N-terminal modified cyclopeptidic mimetics of ApolloTBM as inhibitors of TRF2. Issue 21 (1st November 2020) - Chen, Xia; Dong, Yao; Guo, Tianyue; Yang, Chao-Yie; Chen, Yong; Sun, Haiying
Graphical abstract: Highlights: Peptidic TRF2 inhibitors with C-terminal modifications were reported. Binding affinities were improved and peptidic characteristics were decreased. Binding mode of the designed compounds was predicted. Abstract: Telomeric repeat binding factor 2 (TRF2) plays an important role in protecting telomeres from being recognized as DNA breaks. TRF2 performs its telomere protecting functions partially by recruiting a number of accessory proteins to telomeres through its TRF homology (TFRH) domain. Identification of small molecular compounds which can bind to the TRFH domain of TRF2 and block the interactions between TRF2 and its associated proteins is crucial for elucidating the molecular mechanisms of these protein–protein interactions. Using a previously identified peptidic mimetic of ApolloTBM as a lead compound, we designed and synthesized a series of novel TRF2 inhibitors by non-peptidic modifications of the N -terminal residues. These compounds can maintain the binding affinities to TRF2 but have much reduced peptidic characteristics compared to the lead compound.